PENGUPAHAN DIBAWAH UPAH MINIMUM BAGI USAHA MIKRO KECIL DAN MENENGAH (UMKM) MENURUT PERATURAN PEMERINTAH NOMOR 36 TAHUN 2021 TENTANG PENGUPAHAN - Anggara, Salha Raafi (Universitas 17 Agustus 1945 Samarinda, 2022)
The results of the study show that legally it is emphasized that employers/companies are prohibited from paying wages lower than the minimum wage, but there are exceptions to the minimum wage provisions, the exception to the minimum wage only applies to micro businesses and small businesses, not to medium enterprises. Micro and small businesses in question must meet the criteria set by law, with the condition that the wage value must be above 50% of the average consumption rate at the provincial level and above 25% of the poverty line at the provincial level. For entrepreneurs/enterprises (excluding micro and small businesses) and workers/laborers who have entered into work agreements/agreements, in particular, the value of the wages stipulated in the agreement is lower than the stipulated minimum wage. Then the agreement is null and void by law and wage arrangements must be carried out under statutory regulations. Wages are an absolute right for workers that must be met by employers. One of the wage problems that exist in Indonesia is related to the minimum wage, namely that there are still many workers/laborers who earn wages below the minimum wage provisions, including workers in the Micro, Small, and Medium Enterprises (MSMEs) sector, there are still many entrepreneurs in the MSME sector who base their the wage standard for workers is based on the financial capacity of the business, excluding the provisions of the minimum wage scale.The type of research used in this paper is a type of normative legal research or library law research with a statutory regulation approach. Abstract